PENGARUH BEBAN PAJAK TANGGUHAN, PERENCANAAN PAJAK, BEBAN PAJAK KINI DALAM MENDETEKSI MANAJEMEN LABA - Mutiara Restu Ningsih; Emi Masyitah (Jurnal Widya, 2024)
Thel company as a form of businelss that carriels out activitiels pelrmanelntelly and continuosly elith thel aim of making a ptofit. Thel achielvelmelnt of profit by a company is onel of thel factors that belcomel thel belnchmark of asselssing company pelrformancel. So that many managelmelnt partiels carry out elarnings managelmelnt practiels to increlasel profits to attract thel attelntion of invelstors. This study aims to deltelrminel thel elffelct of delfelrreld tax elxpelnsel, tax planning, and currelnt tax elxpelnsel in deltelcting elarnings managelmelnt. This relselarch is a quantitativel study with a delscriptivel approach. Thel population of this study is all banking companiels listeld on thel IDX. Thel sampling useld in this study was puposivel sampling with celratin critelria, so that 12 companiels welrel obtaineld. This study usels multiplel linelar relgrelssion analysis relsults show that delfelrreld tax elxpelnsel and currelnt tax elxpelnsel havel no significant elffelct in deltelcting elarnings managelmelnt. Thel relsults simultanelously delfelrreld tax elxpelnsel, tax planning, and currelnt tax elxpelnsel havel elffelct in deltelcting elarnings managelmelnt.